AGRADEÇO MUITO QUEM MI AJUDAR :-)
Anexos:
![](https://pt-static.z-dn.net/files/d5c/0655fe6a4637ccbde5701188b57c9776.jpg)
JEANRUAN18:
só a questão 5 mesmo
Soluções para a tarefa
Respondido por
0
2⁰ - (-2)³ / 2² - 2⁰, sabendo que 2⁰ = 1 // (-2)³ = -8 // 2² = 4, e substituindo na expressão, temos:
[1 - (-8)] / (4 - 1) = (1 + 8) / 3 = 9/3 = 3 ==>> LETRA C
[1 - (-8)] / (4 - 1) = (1 + 8) / 3 = 9/3 = 3 ==>> LETRA C
Perguntas interessantes
Português,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Química,
1 ano atrás
Ed. Técnica,
1 ano atrás
Matemática,
1 ano atrás